Corporate social responsibility of Maqasid Al-Shari’ah in shari’ah compliant companies / Nurul Fatihah Ilias, Roshima Said, Noorain Omar - Said, Roshima; Said, Roshima; Omar, Noorain (Institute of Research Management & Innovation (IRMI), 2014)
The awareness and understanding of Corporate Social Responsibility (CSR) in Malaysia have increased and also been used as a mechanism to attract foreign investors. Due to that, the Shari’ah Compliant Companies’ activities must be in accordance to Islamic principle and the disclosure also must be related to the Islamic value. Hence, this study attempts to examine the influence of Maqasid Al-SharVah elements on CSR Maqasid Al- Shari’ah. Furthermore, the study intends to examine the influence of CSR themes on CSR Maqasid Al-Shari’ah. The CSR Maqasid Al-Shari’ah disclosure checklist was developed and sent to experts to verify all the selected items. Initially, the checklist consists of 86 items, and after take into consideration the experts’ opinions (academia and practitioners), the final checklist with 65 items has been established. Content analysis was used in order to construct the CSR Maqasid Al-Shari’ah Index. The unit of analysis for this study is the annual report of 80 Shari ’ah Compliant companies on Main Board of Bursa Malaysia for the year ended 2012. The result implies that Faith element has the most influence on CSR Maqasid Al-Shari ’ah, followed by Intellect, Human Self, Posterity and Wealth element. The finding of the study also shows that human resource is the most significant theme influencing CSR Maqasid Al-Shari’ah, followed by environment, community and product. These empirical results provide evidence that CSR themes do influence CSR Maqasid-Al-Shari'ah. The findings also indicate that the CSR Maqasid Al-Shari’ah disclosure level is relatively low. The empirical evidence from the research could contribute to prior related studies on Islamic CSR and the disclosure checklist is expected to become a benchmark for application of ideal Islamic CSR.